Antibiotic Resistance Patterns of Bacterial Pathogens Associated with Lower Respiratory Tract Infections - Bhatta, Dharm Raj; Hamal, Deependra; Shrestha, Rajani; Nayak, Niranjan (Nepal Journal of Medical Sciences, 2023)
Introduction: Respiratory tract infections are one of the most common and serious health problems in developing countries. Increasing incidences of multidrug-resistant isolates from cases of lower respiratory tract infections have been reported. This study was conducted to determine the bacterial pathogens associated with lower respiratory tract infections with their antibiotic resistance pattern in a tertiary care hospital in Western Nepal. Methods: This hospital-based cross-sectional study was conducted among patients of Manipal Teaching Hospital, Pokhara, Nepal, from August 2022 to October 2022. A total of 376 specimens from the lower respiratory tract were included in this study. Processing of samples, isolation, identification and antibiotic sensitivity test of the bacterial pathogens was performed by standard methods. Results: Respiratory pathogens were recovered in 68 samples. Gram-negative bacteria were isolated in 55 cases and Gram-positive bacteria in 13 cases. Acinetobacter species (42.6%), Staphylococcus aureus (16.9%) and Pseudomonas aeruginosa (13.9%) were the three most common pathogens isolated. The majority of the Gram-negative isolates were susceptible to tigecycline and colistin. Among S. aureus isolates, 54.5% (6/11) were methicillin-resistant Staphylococcus aureus. Conclusion: Gram-negative bacteria were predominantly associated with lower respiratory tract infections with Acinetobacter species as the most common pathogen. Increasing antibiotic resistance was recorded among the pathogens and is alarming. Regular surveillance of pathogens and antibiotic resistance patterns is needed for better management of the patients.